Head to Head: The COming Economic Battle Among Japan, Europe and America - Lester Thurow; THUROW (Lester) (New York William Morrow and Company, 1992)
Head to Head: The Coming Economic Battle Among Japan, Europe & America With the dismantling of the Berlin Wall in 1989 and the implosion of the USSR in 1991, the Cold War era has ended. Immediately, a new economic struggle begins. Three economic superpowers emerge, each playing the game of capitalism in a strikingly different manner. And for the first time, the United States is the second largest economy in the world. As the domestic economy stagnates and the deficit financing of the federal government escalates, many Americans see themselves at a turning point. And well they might. In Head to Head, one of America's most influential economists provides his dynamic assessment of the emerging economic landscape: the rules of this new three-way competition; the strengths and weaknesses of the players; the information we need to win. Head to Head is full of surprises; one attribute of the new competition is that radical new skills and radical new ways of thinking are vital to success. For example:. Competition and Cooperation. In the 1990s, there will be no clear winners, but losers might be destroyed. The ability to cooperate effectively with your direct adversary will be a requisite for survival. Resources. If we are to thrive in this new environment, our whole notion of essential resources must be overhauled before the year 2000. Key Industries. There are seven key industries vital to the maintenance of a high standard of living. How can we maintain competitiveness in those industries over the coming decade and beyond? Education. Education is the most potent weapon of the new warfare. How can we close the education gap? Teams. How can Americans learn to become team players in new and unfamiliar ways?
Keywords: International Economic Relations; Economic History; Economic Policy